RstA Is a Major Regulator of Clostridioides difficile Toxin Production and Motility - Adrianne N. Edwards (American Society for Microbiology, 2019)
ABSTRACT Clostridioides difficile infection (CDI) is a toxin-mediated diarrheal disease. Several factors have been identified that influence the production of the two major C. difficile toxins, TcdA and TcdB, but prior published evidence suggested that additional unknown factors were involved in toxin regulation. Previously, we identified a C. difficile regulator, RstA, that promotes sporulation and represses motility and toxin production. We observed that the predicted DNA-binding domain of RstA was required for RstA-dependent repression of toxin genes, motility genes, and rstA transcription. In this study, we further investigated the regulation of toxin and motility gene expression by RstA. DNA pulldown assays confirmed that RstA directly binds the rstA promoter via the predicted DNA-binding domain. Through mutational analysis of the rstA promoter, we identified several nucleotides that are important for RstA-dependent transcriptional regulation. Further, we observed that RstA directly binds and regulates the promoters of the toxin genes tcdA and tcdB, as well as the promoters for the sigD and tcdR genes, which encode regulators of toxin gene expression. Complementation analyses with the Clostridium perfringens RstA ortholog and a multispecies chimeric RstA protein revealed that the C. difficile C-terminal domain is required for RstA DNA-binding activity, suggesting that species-specific signaling controls RstA function. Our data demonstrate that RstA is a transcriptional repressor that autoregulates its own expression and directly inhibits transcription of the two toxin genes and two positive toxin regulators, thereby acting at multiple regulatory points to control toxin production. IMPORTANCE Clostridioides difficile is an anaerobic, gastrointestinal pathogen of humans and other mammals. C. difficile produces two major toxins, TcdA and TcdB, which cause the symptoms of the disease, and forms dormant endospores to survive the aerobic environment outside the host. A recently discovered regulatory factor, RstA, inhibits toxin production and positively influences spore formation. Herein, we determine that RstA directly binds its own promoter DNA to repress its own gene transcription. In addition, our data demonstrate that RstA directly represses toxin gene expression and gene expression of two toxin gene activators, TcdR and SigD, creating a complex regulatory network to tightly control toxin production. This study provides a novel regulatory link between C. difficile sporulation and toxin production. Further, our data suggest that C. difficile toxin production is regulated through a direct, species-specific sensing mechanism.